Early Signs of Fracture Repair in the Human Rib Cage: Implications for Forensic Casework1. Issue 3 (19th September 2018) - Rubin, Katie M.; Stock, Michala K.
Abstract: The decomposed body of a woman discovered beneath a collapsed structure was examined at the C.A. Pound Human Identification Laboratory. Despite a mix of rib fractures with and without indications of healing, it is most likely that all fractures occurred as a result of a single, compressive event. Signs of intramembranous, and possibly direct, fracture healing at the incomplete fractures without signs of endochondral ossification at the complete fractures suggest the individual died very shortly—but not immediately—after injury. Given the case circumstances, the findings inform immediate cause of death. This case study highlights that differential healing as a result of a single event is possible. Further, it illustrates the importance of careful examination of micro‐discontinuities/cracks that can occur in association with major fractures. Fracture healing and dating data are discussed, as is the possible need for critical evaluation of the antemortem/perimortem boundary.